Emulating the MERINO randomised control trial using data from an observational cohort and trial of rapid diagnostic (BSI-FOO). - Rebecca N Evans; Jessica Harris; Chris A Rogers; Alasdair MacGowan (PLoS ONE)
Objective The aim of this study was to emulate the MERINO trial of piperacillin-tazobactam vs meropenem for the definitive treatment of bloodstream infection (BSI) caused by ceftriaxone-nonsusceptible E coli or Klebsiella spp. Methods Data from an observational study of BSI and a randomised controlled trial of a rapid diagnostic in BSI were used to emulate the MERINO trial. The primary outcome of the emulated trial was 28-day mortality after blood culture. Outcomes were compared using logistic regression adjusted for propensity score for emulated intervention. Results Of the 6,371 observational study and RCT participants, 1,968 had a bloodstream infection with E. coli or Klebsiella spp. of which 121 met the eligibility criteria. In the emulated trial, a total of 14/82 patients (17.1%) allocated to piperacillin-tazobactam met the primary outcome compared with 6/39 (15.4%) in the meropenem group (unadjusted odds ratio 1.13 (95% CI 0.40 to 3.21)). After adjustment for propensity score, the odds ratio increased to 1.31 (95% CI 0.40 to 4.26). This difference is in the same direction but of a smaller magnitudethan observed in the MERINO trial, where 30-day mortality was met by 23/187 patients (12.3%) in the piperacillin-tazobactam and 7/191 (3.7%) in the meropenem group (unadjusted odds ratio of 3.69 (95% CI 1.48 to 10.41)). Conclusions The mortality rate in an emulated trial population was more than double the mortality rate in the MERINO trial. The methodology used attempts to address the concern that previous results could be explained by biases such as selection bias and uncontrolled confounding and provides information on how a trial such as the MERINO trial may have performed in the NHS.